Can brand ambassadors influence product loyalty: perceptions on globacom mobile network advertisements (2018)
Studies in Nigeria have not fully shown the effect of using celebrities and how celebrities can effectively change the attitude of the consumers towards a brand. Based on this notion, the study examined audience perception of celebrity endorsement on product advertising and its influence on brand loyalty. Through a mixed method design, the study used questionnaire and structured interview. The respondents perceived the use of celebrities in Globacom adverts necessary because these celebrities are persuasive, entertaining and experienced. This further enhances awareness and sales for the product. Globacom celebrities have a good interpersonal relation with Globacom customers as they prefer celebrity endorsed products’ adverts to non-celebrity endorsed products’ adverts which influence their purchase. Globacom celebrities are liked and perceived as highly credible; hence celebrities that match products’ brand image should be endorsed to promote the brand in order to influence consumers’ purchase and loyalty to the products.